Information Ethics education in Southern Africa - Coetzee Bester; Johannes Britz; Bradley J. Wiles (Informatio)
This article proposes the Information Ethics Curriculum Model, a university-level educational heuristic aimed at promoting safe, responsible, and advantageous information use in multicultural settings across Southern Africa. The Model is designed to raise awareness of the ethical challenges posed by modern information and communication technologies (ICTs) amongst inhabitants of the Southern African region. It also seeks to equip students with the knowledge, understanding, and skills needed in their search for and use of information critical to their own and others’ empowerment. The article describes the Model’s theoretical and conceptual foundation and provides basic guidelines for applying the Model at undergraduate and graduate levels.